Surgical Treatment of Abdominal Aortic Aneurysms. A Retrospective Study. - Edmond Nuellari; Saimir Kuci; Albana Kenga; Denis Kosovrasti; Alfred Ibrahimi; Ervin Bejko (Albanian Journal of Trauma and Emergency Surgery, 2024)
Introduction: Surgical treatment of abdominal aortic aneurysms poses a significant challenge in the field of vascular surgery, with numerous factors influencing operative technique and surgical outcome.